Diagnostic indicators for peptic ulcer perforation at a tertiary care hospital in Thailand - Chutikarn Suriya (2018)
Introduction: Limited data currently exists regarding the diagnostic indicators of peptic ulcer perforation for early detection among patients in Thailand. Delayed diagnosis and treatment for an ulcer can be life-threatening, resulting in shock or death. Objective: To determine the diagnostic indicators of peptic ulcer perforation. Material and methods: A cohort study was conducted in a tertiary care hospital in Thailand from 2005 to 2009. Peptic ulcer patients aged 15 years and over admitted to the surgical department were included. The diagnostic indicators used criteria of the patients' final diagnoses and operations, coded according to the International Statistical Classification of Diseases and Related Health Problems, 10th Revision, which included patient profiles, gender, age, coexisting illnesses, personal habits, signs and symptoms, laboratory investigations, radiological finding, and treatment role. Exponential risk regression analyses to obtain relative risk (RR) estimates for diagnostic indicators were analyzed using Stata® statistical software package, version 11 (StataCorp LP, College Station, TX). Results: The study included 1290 patients. Of these, 57% reported perforated peptic ulcer. Multivariate analysis showed five diagnostic indicators: signs and symptoms including intense abdominal pain (RR = 1.53, 95% confidence interval [CI] 1.14-2.06), tenderness (RR = 1.94, 95% CI 1.17-3.21), and guarding (RR = 1.52, 95% CI 1.05-2.20); X-ray with free air (RR = 2.80, 95% CI 2.08-3.77); and referral from other hospitals (RR = 1.37, 95% CI 1.03-1.82). Conclusion: Five diagnostic indicators for peptic ulcer perforation monitoring were suggested from this study. Improving diagnostic indicators for medical care may improve the outcome of patients that have perforated peptic ulcer. © 2011 Suriya et al, publisher and licensee Dove Medical Press Ltd.